Historicizing theories, identities, and nations - Darnell, Regna; Gleach, Frederic W. (Frederic Wright), 1960- (Histories of anthropology annual, 2017)
The Histories of Anthropology Annual presents diverse perspectives on the discipline's history within a global context, with a goal of increasing awareness and use of historical approaches in teaching, learning, and conducting anthropology. The series includes critical, comparative, analytical, and narrative studies involving all aspects and subfields of anthropology.